2000
DOI: 10.1089/109629600750018150
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Multiple Organ Dysfunction Syndrome: Lessons Learned and Future Prospects

Abstract: Gram-negative bacteria commonly cause serious infections in hospitalized patients, and those that lead to bacteremic episodes and sepsis syndrome are associated with the highest mortality rate. Sepsis syndrome frequently progresses to multisystem organ dysfunction and failure, with as many as 400,000 cases occurring annually. Unfortunately, the associated mortality rate remains about 40%. Lipopolysaccharide (LPS, endotoxin), an integral component of the gram-negative bacterial outer membrane, plays a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Proinflammatory cytokines are known to directly contribute to sepsis-induced myocardial depression and other alterations in hemodynamic function observed in septic patients as well as in experimental models of sepsis (9,17,23,25). Most prior studies have focused on macrophages and monocytes as the primary cell types driving the proinflammatory response during sepsis (8,10,21). In our prior report, we showed that depletion of NK and CD8 ϩ T cells significantly contributes to the resistance of ␤2M/␣AsGM1 mice to CLP-induced mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Proinflammatory cytokines are known to directly contribute to sepsis-induced myocardial depression and other alterations in hemodynamic function observed in septic patients as well as in experimental models of sepsis (9,17,23,25). Most prior studies have focused on macrophages and monocytes as the primary cell types driving the proinflammatory response during sepsis (8,10,21). In our prior report, we showed that depletion of NK and CD8 ϩ T cells significantly contributes to the resistance of ␤2M/␣AsGM1 mice to CLP-induced mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Lipopolysaccharide from the cell wall of Gram‐negative bacteria has for a long time been known as a very potent endotoxin [2] and is recognized by the immune cells through the TLR4. Peptidoglycan is a bacterial cell wall component found in both Gram‐positive and Gram‐negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis occurs as a dysregulated inflammatory response to infection that can cause multiple‐organ dysfunction syndrome (MODS), circulatory failure and eventually death [1]. Among the bacterial components contributing to the development of sepsis, Gram‐negative bacterial lipopolysaccharide (LPS) has been thought to be the triggering molecule of the excessive inflammatory response [2]. When bacteria are allowed to enter into the blood stream and mammalian tissue during an infection, endotoxins such as LPS are recognized by macrophages by virtue of Toll‐like receptors (TLRs).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines (TNF-α and IL-1) secreted by macrophages were centrally involved in the inflammatory responses. Suppressing the activation of macrophages could reduce the production of cytokines and subsequently relieve systemic or local inflammatory injury (Dunn, 2000;Kherani et al, 2004;Leiro et al, 2002;Park et al, 2004). Bertelli et al (2001) demonstrated that RESV could modulate the production of vascular cell adhesion molecule-1 (VCAM-1) in TNF-α stimulated endothelial cells and inhibit the increase of vascular permeability induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%